Arterial-Arteriolar Sclerosis Is Independently Associated With Poor Renal Outcome in IgA Nephropathy Patients - Lingqiu Dong (Frontiers Media S.A., 2021)
Aim: This study aimed to investigate the clinicopathological features and prognosis of immunoglobulin A nephropathy (IgAN) with arterial-arteriolar sclerosis (AS).Methods: Patients with biopsy-proven IgAN from the West China Hospital of Sichuan University were retrospectively enrolled. Clinicopathological features were collected. Patients were categorized based on the presence and the severity of the AS. All the patients were regularly followed-up until a composite end point. The correlation between AS and prognosis of IgAN was assessed.Results: A total of 1,424 patients were recruited and followed for 60.0 ± 28.7 months. Patients with AS tended to have older age, higher blood pressure, heavier proteinuria, higher serum creatinine, uric acid, and total triglyceride (TG). Meanwhile, they were more likely to have a lower estimated glomerular filtration rate (eGFR), hemoglobin, and albumin. At the end of follow-up, 126 patients in the AS group and 47 patients in the non-AS group had reached the composite end point (p < 0.001). AS was associated with the renal outcome (log-rank p < 0.001) and was an independent risk factor for the progression of IgAN (p = 0.049). The severity of AS was associated with renal outcomes (log-rank p < 0.001) and there was a trend that it might serve as an independent risk marker for progression of IgAN. In the subgroup analysis, patients presenting with AS and lower eGFR, albumin, and hemoglobin or higher proteinuria, uric acid, and TG had a significant trend for a shorter time to reach the end point (log-rank p < 0.001).Conclusion: AS was commonly seen in patients with IgAN and was independently associated with the poor prognosis.